TiO2 with super narrow bandgap achieved in one-step single-mode magnetic microwave induced plasma treatment. (1st March 2020) - Kato, Kunihiko; Xin, Yunzi; Shirai, Takashi
Abstract: TiO2 with super narrow bandgap (1.1 eV∼) are successfully synthesized via a facile and novel one-step single-mode magnetic microwave induced plasma treatment. The selectively surface Ti 3+ -doping on obtained TiO2 as trapping centers which significantly restrain the photo-excited carrier recombination and achieve the enhancement of visible-light photocatalytic performance. In addition, the surface chemical composition of TiOx is precisely controlled in a wide region of 1.19 <  x  < 1.92 during one-step reaction. A detailed XPS analysis reveals that the surface formed Ti 3+ shows highly thermal/chemical stability even through high-temperature treatment (∼800 °C) in oxidative atmosphere and photocatalytic reaction. Graphical abstract: Image, graphical abstract